1992
DOI: 10.1007/bf02733953
|View full text |Cite
|
Sign up to set email alerts
|

Stenting of the iliac arteries with the palmaz stent: Experience from a multicenter trial

Abstract: Balloon-expandable, intraluminal stenting of the iliac arteries with the Palmaz stent was the subject of a multicenter study for 4 years. A total of 486 patients underwent 587 procedures. Four hundred and five patients had unilateral and 81 had bilateral iliac stent placements. Follow-up ranged from 1 to 48 months (mean 13.3 +/- 11 months). Sustained clinical benefit of the treated patients was obtained in 90.9% at 1 year, 84.1% at 2 years, and 68.6% at 43 months. Angiographic patency rate was 92%. Diabetes me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0
3

Year Published

1995
1995
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(106 citation statements)
references
References 15 publications
5
96
0
3
Order By: Relevance
“…4 Similar results were reported by Gunther at al 5,6 and Murphy at al 7 Palmaz at al reported that the patency rate for the Palmaz stent at 8.7 months was 92%, and others have made a similar observation. [8][9][10][11][12] In the present study, the initial procedural success and patency rates (95% and 97%, respectively) are comparable with previous reports [4][5][6][7][8][9][10][11][12] and are considered equal to, or even superior to, the results obtained with the Wallstent or Palmaz stents.…”
Section: Discussionsupporting
confidence: 91%
“…4 Similar results were reported by Gunther at al 5,6 and Murphy at al 7 Palmaz at al reported that the patency rate for the Palmaz stent at 8.7 months was 92%, and others have made a similar observation. [8][9][10][11][12] In the present study, the initial procedural success and patency rates (95% and 97%, respectively) are comparable with previous reports [4][5][6][7][8][9][10][11][12] and are considered equal to, or even superior to, the results obtained with the Wallstent or Palmaz stents.…”
Section: Discussionsupporting
confidence: 91%
“…A single stent graft stenosis, which occurred at 8 months' follow-up, responded to percutaneous balloon angioplasty and remained patent for 23 months. 48 The logical extension of transluminally placed endovascular grafting using covered stents and stent-fixed prosthetic conduits to treat more complex arterial lesions has followed a relatively ordered course with the development of new devices and animal models in which to test these devices. 4955 The earliest clinical experience with endovascular grafts is attributed to Volodos in Russia, who described his experience with self-expanding endovascular grafts for the treatment of a thoracic aortic aneurysm and aortoiliac occlusive disease.…”
Section: Penetrating and Latrogenic Arterial Traumamentioning
confidence: 99%
“…For a variety of peripheral stenoses, intravascular stents have been proven to be useful therapeutic adjuncts to percutaneous balloon angioplasty procedure [14]. In addition, there is evidence that endovascular stenting, as primary therapy, provides a predictable improvement in initial lumen diameter, avoidance of elastic recoil, and subsequent lumen reduction by restenosis [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Balloon angioplasty is a proven treatment for children with recoarctation of the aorta [9,16]. However, there is little known about balloon angioplasty for adult recoarcta- tion of the aorta.…”
Section: Discussionmentioning
confidence: 99%